Propofol versus Desflurane in Moyamoya Disease Patients—A Pilot Study - Ankolekar, Ronak R.; Kaur, Kirandeep; Jangra, Kiran; Aggarwal, Ashish; Panda, Nidhi B.; Bhagat, Hemant; Barik, Amiya K. (Asian Journal of Neurosurgery, 2023)
Objectives The choice of inhalational or intravenous anesthetic agents is debatable in neurosurgical patients. Desflurane, a cerebral vasodilator, may be advantageous in ischemic cerebral pathologies. Hence, we planned to compare desflurane and propofol in patients with moyamoya disease (MMD) with the objective of comparing neurological outcomes.Materials and Methods This prospective pilot trial was initiated after institutional ethics committee approval. Patients with MMD undergoing revascularization surgery were randomized into two groups receiving either desflurane or propofol intraoperatively. Neurological outcomes were assessed using a modified Rankin score (mRS) at discharge and an extended Glasgow outcome score (GOS-E) at 1 month. Intraoperative parameters, including hemodynamic parameters, end-tidal carbon dioxide, entropy, intraoperative brain relaxation scores (BRS), and rescue measures for brain relaxation, were compared.Statistical Analysis The normality of quantitative data was checked using Kolmogorov–Smirnov tests of normality. Normally distributed data were compared using unpaired t-tests, skewed data using Mann–Whitney U tests, and categorical variables using chi-squared tests.Results A total of 17 patients were randomized, 10 in the desflurane and 7 in the propofol group. mRS (1.3 ± 0.6 and 1.14 ± 0.4, p = 0.450) and GOS-E (6.7 ± 0.6 and 6.85 ± 0.5, p = 0.45) were comparable between desflurane and propofol groups, respectively. BRS was significantly higher in the desflurane group (3.6 ± 0.5) compared to the propofol group (2.1 ± 0.3, p = 0.001), with a significant number of patients requiring rescue measures in the desflurane group (70%, p < 0.001). Other outcome parameters were comparable (p > 0.05).Conclusion We conclude that postoperative neurological outcomes were comparable with using either an anesthetic agent, desflurane, or propofol in MMD patients undergoing revascularization surgery. Maintenance of anesthesia with propofol had significantly superior surgical field conditions.
Keywords: anesthesia; desflurane; moyamoya disease; propofol